Role of Rice stripe virus NSvc4 in cell-to-cell movement and symptom development in Nicotiana benthamiana - Xu, Yi; Zhou, Xueping (Frontiers in Plant Science, 2012)
Our previous work has demonstrated that the NSvc4 protein of Rice stripe virus (RSV) functions as a cell-to-cell movement protein. However, the mechanisms whereby RSV traffics through plasmodesmata (PD) are unknown. Here we provide evidence that the NSvc4 moves on the actin filament and endoplasmic reticulum network, but not microtubules, to reach cell wall PD. Disruption of cytoskeleton using different inhibitors altered NSvc4 localization to PD, thus impeding RSV infection of Nicotiana benthamiana. Sequence analyses and deletion mutagenesis experiment revealed that the N-terminal 125 amino acids (AAs) of the NSvc4 determine PD targeting and that a transmembrane domain spanning AAs 106–125 is critical for PD localization. We also found that the NSvc4 protein can localize to chloroplasts in infected cells. Analyses using deletion mutants revealed that the N-terminal 73 AAs are essential for chloroplast localization. Furthermore, expression of NSvc4 from a Potato virus X (PVX) vector resulted in more severe disease symptoms than PVX alone in systemically infected N. benthamiana leaves. Expression of NSvc4 in Spodoptera frugiperda 9 cells did not elicit tubule formation, but instead resulted in punctate foci at the plasma membrane. These findings shed new light on our understanding of the movement mechanisms whereby RSV infects host plants.